Implementation of Islamic Values in Financial Management - Astutik, Winda (http://jagadalimussirry.com/, 2020)
This study aims to determine the nature of Islamic values, the nature of financial management and the implementation of Islamic values ​​in financial management, so that Muslims are not mistaken in calculating their financial lives which are detrimental and making a prosperous life. This research belongs to the type of literature study research by finding relevant theory references related to the implementation of Islamic values ​​in financial management. The results of the study indicate that a Muslim needs to understand and practice the values ​​of Islam which include creeds, sharia and morals in all aspects of life, including in regulating finances. Al-Qur'an has explained how to manage the economy with all its descriptions, which essentially includes two things, namely the ability to find material and the ability to spend it. A Muslim is required to obtain everything in a lawful way, including getting material. In order to create a good mentality related to lifestyle, Allah Subhanahu wa Ta'ala instructs people to fulfill their needs in a modest, middle-class, and not wasteful manner in spending. Talks about spending material can be divided into a number of materials, allocated for routine expenses, alms and investment hereafter.